Tratamento eletroquímico do antibiótico cloridrato de tetraciclina em efluente sintético - Rossi, José Rafael (2017)
The accumulation of certain organic pollutants in the environment has become a globally relevant environmental aspect, due to the wide use of these compounds and their persistence to biodegradation. The fact that many of these organic pollutants are resistant to biochemical degradation leads to the search for alternative techniques. In this context, electrochemical treatments, in particular anodic oxidation, may be a promising alternative for the degradation of such compounds. The present work had as main objective to evaluate the treatment of synthetic effluent in the degradation of the tetracycline hydrochloride drug, antibiotic, widely used in human and veterinary medicine, by means of the anodic oxidation system, applying as anode the electrode, Ti/Ru0,3Ti0,7O2. The electrochemical degradation assays of tetracycline hydrochloride were carried out in a shaking system in an electrochemical cell containing a dimensionally stable electrode, as an anode, as a cathode a porous titanium plate and a saturated Ag / AgCl electrode as reference, capable of 1000 mL of solution. The statistical design applied to the drug degradation assays was the Central Rotational Compound Design. The independent variables applied were: current, crude effluent pH and electrooxidation time. For characterization of the effluent and to verify the degradation of the compound, chemical oxygen demand (COD), pH, electrical conductivity, ultraviolet-visible absorption spectrophotometry and high performance liquid chromatography were performed. The crude effluent had a mean COD of 122 mg O2 L-1, a pH of 4.02, an electrical conductivity of 30.72 mS cm-1 and a tetracycline hydrochloride concentration of 87.20 mg L-1. After treatment of the effluent it was observed that there was no variation of pH and electrical conductivity. The electrochemical treatment showed a low removal of COD, but in certain tests the tetracycline hydrochloride was not detected by the high performance liquid chromatography analysis characterizing the formation of fragments without mineralization of the drug. The best treatment efficiency points were E4, E8 and E12, which present high currents and electrooxidation time, and the pH of the effluent did not influence the removal efficiency of tetracycline hydrochloride. In order to evaluate the toxicity of the degradation fragments, toxicity tests were carried out against the microcrack Artemia salina, verifying that the effluent showed no toxicity and its decrease was not accentuated after the treatment. Finally, to identify the bacterial activity of tetracycline hydrochloride and its degradation products after treatment, bacterial sensitivity tests with the bacteria Escherichia coli and Staphylococcus aureus were performed, noting that the effluents after the electrochemical treatment did not present antibiotic activities for the bacteria selected.